The Functional Characterization of Epigenetically Related lncRNAs Involved in Dysregulated CeRNA–CeRNA Networks Across Eight Cancer Types - Xu, Dahua; Wang, Liqiang; Pang, Sainan; Cao, Meng; Wang, Wenxiang; Yu, Xiaorong; Xu, Zhizhou; Xu, Jiankai; Wang, Hong; Lu, Jianping; Li, Kongning (Frontiers in Cell and Developmental Biology, 2021)
Numerous studies have demonstrated that lncRNAs could compete with other RNAs to bind miRNAs, as competing endogenous RNAs (ceRNAs), to regulate each other. On the other hand, ceRNAs were found to be recurrently dysregulated in cancer status. However, limited studies considered the upstream epigenetic regulatory factors which disrupted the normal competing mechanism. In the present study, we constructed the lncRNA-associated dysregulated ceRNA networks across 8 cancer types. LncRNAs in the individual dysregulated network and pan-cancer core dysregulated ceRNA subnetwork were found to play more important roles than mRNAs. Integrating lncRNA methylation profiles, we identified 49 epigenetically related (ER) lncRNAs involved in the dysregulated ceRNA networks, including 18 epigenetically activated (EA) lncRNAs, 18 epigenetically silenced (ES) lncRNAs and 13 rewired ER lncRNAs across 8 cancer types. Furthermore, we evaluated the epigenetic regulating patterns of these lncRNAs and screened 9 pan-cancer ER lncRNAs (6 EA and 3 ES lncRNAs). The 9-lncRNAs were found to regulate the cancer hallmarks by competing with mRNAs. Moreover, we found that integrating the expression and methylation profiles of the 9-lncRNAs could predict cancer incidence in 8 cancer types robustly and the cancer outcome of several cancer types. These results provide an improved understanding of methylation regulation to ceRNA and offer novel potential molecular therapeutic targets for the diagnosis and prognosis across different cancer types.